2013
DOI: 10.1016/j.cnsns.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian descriptors: A method for revealing phase space structures of general time dependent dynamical systems

Abstract: In this paper we develop new techniques for revealing geometrical structures in phase space that are valid for aperiodically time dependent dynamical systems, which we refer to as Lagrangian descriptors. These quantities are based on the integration, for a finite time, along trajectories of an intrinsic bounded, positive geometrical and/or physical property of the trajectory itself. We discuss a general methodology for constructing Lagrangian descriptors, and we discuss a "heuristic argument" that explains why… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
221
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(225 citation statements)
references
References 55 publications
4
221
0
Order By: Relevance
“…[26,15]). The choice of this tool versus others mentioned above, such as for instance FTLE, is based on the advantages discussed in the literature [27,28,29,30]. These are related to its accuracy, ability to detect Lagrangian features of the true ocean state, computational 115 efficiency and programming simplicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[26,15]). The choice of this tool versus others mentioned above, such as for instance FTLE, is based on the advantages discussed in the literature [27,28,29,30]. These are related to its accuracy, ability to detect Lagrangian features of the true ocean state, computational 115 efficiency and programming simplicity.…”
mentioning
confidence: 99%
“…The initial green circle approaches the coast line following the stable manifold, and elongates itself along the unstable manifold. Figure 2D) provides further details of the underlying skeleton, by plotting two unstable A skeleton of the stable and unstable manifolds of hyperbolic trajectories in time dependent flows can be constructed with the technique that is referred to as Lagrangian descriptors, based on the function M (see [40,26,27]), defined as follows: Another tool for revealing invariant manifolds in time dependent flows, which has been extensively applied in geophysical contexts [12,25,9] In order to deal with Eq. (1), we have assumed that particle motion is mainly horizontal on a sphere of radius R:…”
mentioning
confidence: 99%
“…The importance of the large class of hyperbolic trajectories outlined above is underscored by their effect on the global behavior. For example, it is well known that stable and unstable manifolds form important flow separators in fluid flows, thereby providing a skeleton which distinguishes between regions of anomalous motion [4,[6][7][8][9][10]. Hyperbolic trajectories are entities to which these stable and unstable manifolds are attached, and hence their motion with time governs the time variation of these flow separators.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that such POs can be obtained through a variational procedure based on Lagrangian descriptors (LDs). [36][37][38][39][40][41][42][43][44] The connection of the LD to the construction of POs is presented in Sec. II.…”
Section: Introductionmentioning
confidence: 99%